Kehidupan Muhammad Iqbal dan gagasan sastera Islam = The life of Muhammad Iqbal and Islamic lierature - Yaacob, Adli; Mohd Fadzil, Farrah Syafiqah (Global Academic Excellence (M) Sdn Bhd (GAE), 2021)
This article is about the famous Pakistani poet Muhammad Iqbal. He is a leading figure of this century. His name alone is enough to describe his greatness because many of the leading figures who came after him were influenced by his ideas. When looking into his life comprehensively; his life journey in seeking knowledge, his life struggle in resisting western secular trends and setting the principles of Islamic understanding in a traditional and modern setting as if he were a perfect individual example as an ‘Islamic writer’. He does not specifically mention the term Islamic literature but every stanza of his poetry and prose is a precise reflection of Islamic thought. He contradicted western and communist secular thoughts with his intellectual strength. In one analogy, he says that his action is like the Prophet Ibrahim (a.s)who was not burned by the fire of Namruz; he was not influenced by western culture and was even able to gain control and answer some western questions about Islam. Iqbal believes that art is a sincere expression of one’s conscience. Thus, art has the power of values to educate other human beings. Furthermore, Iqbal stressed that the highest form of art is that which is able to awaken human beings and further cultivate the spirit to rise up to face the trials of life.